Improvised Neonatal Care–Realizing the Gaps in a Disaster Zone. Issue 1 (9th December 2015) - Mendlovic, Joseph; Albukrek, Dov; Dagan, David; Merin, Ofer; Weiser, Giora
Abstract: The treatment of newborns in a disaster zone can be extremely challenging. The effects of the disaster combine with local health care disparity to give these neonates little chance of survival in the event of even minor complications. Rescue teams arriving at such locations must be prepared to handle and to aid these difficult situations using improvisation and ingenuity to overcome many of the unexpected hurdles. A discussion of the difficulties faced in the Philippines following a typhoon and recommendations for future teams are presented. J Mendlovic, D Albukrek, D Dagan, O Merin, G Weiser .Improvised neonatal care‒realizing the gaps in a disaster zone .Prehosp Disaster Med .2016 ;31 (1 ):111 –113 .